PENGARUH SEKTOR PERTANIAN, INDUSTRI PENGOLAHAN, DAN PARIWISATA TERHADAP KEMISKINAN DI JAWA TENGAH TAHUN 2016-2020 - Rohmat, Nur; Indrawati, Lucia Rita (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kota Magelang, 2022)
As a developing country, Indonesia has not been separated from the problem of poverty. Central Java is one of the provinces in Indonesia that has a high number of poor people in Indonesia. Even poverty in Central Java is still a strategic issue that cannot be completely resolved. This study was conducted with the aim of knowing the effect of the output of the agricultural sector, manufacturing industry, and the tourism sector on the number of poor people in Central Java in 2016-2020. This study uses secondary data using a panel regression model. The results of this study indicate that (1) the agricultural sector has a negative and significant effect on poverty in Central Java, (2) the manufacturing sector has an insignificant negative effect on poverty in Central Java, (3) the tourism sector has a negative and insignificant effect on poverty in Central Java, (4) the agricultural sector, the manufacturing sector, and the tourism sector together have a significant influence on poverty in Central Java in 2016-2020.